2017
DOI: 10.1002/alr.22066
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management in endoscopic endonasal skull‐base surgery: a survey of the North American Skull Base Society

Abstract: Background:The objective of this work was to be er understand variations in perioperative management in endoscopic endonasal skull-base surgery (EESBS) and to identify trends in management based upon the practice pa erns of North American Skull Base Society (NASBS) members. Methods:A 29-question survey evaluating perioperative EESBS management was sent to all NASBS members. Responses were analyzed with descriptive statistics. Subgroup analysis was performed based on participant demographics. A Bonferroni corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…To date, there are only retrospective analyses and expert opinion on the risks and recommended best practice for CPAP use after endonasal surgery. [4][5][6] While the pressure supplied by CPAP machines can be controlled and titrated to treat OSA, there have been no studies to date analyzing pressures specifically transmitted to the nasal cavity, paranasal sinuses, or skull base. The goals of this study are to demonstrate the safety of this sensor technology, to validate our cadaveric model in vivo, and to quantify the effect of positive pressure ventilation on the human nasal cavity where physiologic factors such as mucosal edema, secretions, and lung compliance are present.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are only retrospective analyses and expert opinion on the risks and recommended best practice for CPAP use after endonasal surgery. [4][5][6] While the pressure supplied by CPAP machines can be controlled and titrated to treat OSA, there have been no studies to date analyzing pressures specifically transmitted to the nasal cavity, paranasal sinuses, or skull base. The goals of this study are to demonstrate the safety of this sensor technology, to validate our cadaveric model in vivo, and to quantify the effect of positive pressure ventilation on the human nasal cavity where physiologic factors such as mucosal edema, secretions, and lung compliance are present.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] The trend that many are "over working the workhorse," and overusing the NSF was further highlighted in a recent survey of the NASBS in which 50% of surgeons reported used the NSF for low-flow intraoperative CSF leaks in routine transsphenoidal surgery, and another 15% even used it when no leak was encountered. 23 We suspect that this may be related to the technique of routinely harvesting the NSF upfront, which then leads to the conundrum of what to do with a raised NSF at the end of a procedure in cases where an NSF may not actually be needed.…”
Section: Discussionmentioning
confidence: 99%
“…7 A recent survey study likewise found highly variable practice patterns among respondents with respect to skull base surgery. 8…”
Section: Discussionmentioning
confidence: 99%